2003
DOI: 10.1073/pnas.1232343100
|View full text |Cite
|
Sign up to set email alerts
|

Mdm20 protein functions with Nat3 protein to acetylate Tpm1 protein and regulate tropomyosin–actin interactions in budding yeast

Abstract: The evolutionarily conserved Mdm20 protein (Mdm20p) plays an important role in tropomyosin-F-actin interactions that generate actin filaments and cables in budding yeast. However, Mdm20p is not a structural component of actin filaments or cables, and its exact function in cable stability has remained a mystery. Here, we show that cells lacking Mdm20p fail to N-terminally acetylate Tpm1p, an abundant form of tropomyosin that binds and stabilizes actin filaments and cables. The F-actin-binding activity of unacet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
96
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(108 citation statements)
references
References 41 publications
7
96
0
Order By: Relevance
“…Previous studies have observed that an increment in tropomyosin expression partially restores functional defects in actin stress fibers (31,37). In contrast, Tpm1 overexpression in wildtype HeLa cells significantly reduced the area and number of focal adhesions, in agreement with other expressed tropomyosin isoforms (38) and suggestive of a compromised Tpm1 function, most probably by its reduced Nt-acetylation.…”
Section: Tpm1 Overexpression Partially Restores Actin Cytoskeletonsupporting
confidence: 63%
See 3 more Smart Citations
“…Previous studies have observed that an increment in tropomyosin expression partially restores functional defects in actin stress fibers (31,37). In contrast, Tpm1 overexpression in wildtype HeLa cells significantly reduced the area and number of focal adhesions, in agreement with other expressed tropomyosin isoforms (38) and suggestive of a compromised Tpm1 function, most probably by its reduced Nt-acetylation.…”
Section: Tpm1 Overexpression Partially Restores Actin Cytoskeletonsupporting
confidence: 63%
“…Interestingly, NatB mediated Ntacetylation of Nt-unspliced tropomyosin and iMet-retaining forms of actin is conserved in yeast and mammals. NatB-deficient yeast strain exhibit defects in actin cable formation similar to observed in the strains with actin and tropomyosin mutations (10,31). These findings suggest that such defects are caused by the lack of acetylated actin and tropomyosins.…”
Section: Tpm1 Overexpression Partially Restores Actin Cytoskeletonmentioning
confidence: 51%
See 2 more Smart Citations
“…Mutations in these complexes lead to a number of pleiotropic phenotypes, but in recent years, a growing number of these defects have been specifically linked to single protein substrates. For example, telomeric silencing, membrane trafficking, L-A viral assembly, and tropomyosin-actin interactions are mediated by the specific N-terminal acetylation of Orc1, Arl3, gag, and Tpm1, respectively (Tercero and Wickner, 1992;Singer and Shaw, 2003;Behnia et al, 2004;Geissenhoner et al, 2004;Setty et al, 2004). In many of these cases, the loss of acetylation reduces the affinity of these substrates for a partner protein, providing a detailed mechanistic explanation for the observed phenotype.…”
mentioning
confidence: 99%